Optimizing Management Accounting in the Digital Age: Artificial Intelligence for Operational Efficiency and Strategic Decision Making - Putri, Shalsa Billa Eka; Wardani, Farah Arda; Putri, Aprilia Wahana; Kustiwi, Irda Agustin (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The development of digital technology in the era of the Industrial Revolution 4.0 has driven a major transformation in management accounting practices, particularly through the utilization of Artificial Intelligence (AI). This article aims to explore the role of AI in optimizing management accounting, improving operational efficiency, and supporting data-driven strategic decision-making. Using the Systematic Literature Review (SLR) approach, this article examines various recent scientific literatures that discuss the application of AI in accounting information systems, predictive analysis, anomaly detection, and business process automation. The results of the review show that AI integration can accelerate financial reporting, improve information accuracy, and change the role of accountants into strategic partners of management. Previous studies also prove that AI contributes to creating competitive advantages in dynamic sectors such as e-commerce and tourism. Thus, optimizing management accounting through AI not only drives efficiency, but also strengthens the competitiveness of companies in the face of digital market dynamics